STATISTICAL IMAGING STUDIES REGARDING SKELETAL CHANGES IN PATIENTS WITH OPEN BITE - Eugen Silviu Bud; Mariana Păcurar; Alexandru Vlasa; Martha Krisztina; Manuela Chibelean; Evelin Țînț; Bucur Sorana Maria; Gabriel G. Condurache; Anamaria Bud (Romanian Dental Association for Education, 2021)
Orthodontic abnormalities are common in today's population, as the individual is subjected to dietary changes, growth and continuous re-adaptation to environmental conditions. The objectives of this study were to observe the morphological changes of the cervical spine and of the cervical length, together with the severity of the overjet in patients with open bite compared with those with frontal overbite. The average measurement of the inter-incisal distances of the patients with frontal vertical open bite was 6.18 mm. The minimum measurement value was 0.74 mm and the maximum measurement value was 12.24 mm. Steiner angle expresses a high percentage of exaggerated vertical growth (85.3% with increased angle values. The most common morphological changes among patients are simple fusions between two cervical vertebrae, most often the C2 and C3 vertebrae.